2017
DOI: 10.18240/ijo.2017.11.10
|View full text |Cite
|
Sign up to set email alerts
|

Prospective study of Centurion® versus Infiniti® phacoemulsification systems: surgical and visual outcomes

Abstract: CDE is 28.87% less, and VOs are significantly improved, in denser cataracts in the CPS compared with the IPS. The authors recommend the CPS for cases with denser nuclei.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 17 publications
1
13
0
Order By: Relevance
“…concluded that AFS improved the efficiency of phacoemulsification and saved the cumulative dissipated energy (CDE), but Malik and colleagues reported that no significant difference existed in CDE between the two systems with the same phaco tip [ 13 , 15 , 16 ]. Also, results are not entirely consistent across studies, with the conservation of CDE associated with AFS varied from 13.5% to 40% [ 13 , 15 , 17 , 18 ]. However, most studies are conducted on different phacoemulsifiers, which might cause potential bias and reduce the credibility of the results [ 14 , 15 , 17 ].…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…concluded that AFS improved the efficiency of phacoemulsification and saved the cumulative dissipated energy (CDE), but Malik and colleagues reported that no significant difference existed in CDE between the two systems with the same phaco tip [ 13 , 15 , 16 ]. Also, results are not entirely consistent across studies, with the conservation of CDE associated with AFS varied from 13.5% to 40% [ 13 , 15 , 17 , 18 ]. However, most studies are conducted on different phacoemulsifiers, which might cause potential bias and reduce the credibility of the results [ 14 , 15 , 17 ].…”
Section: Introductionmentioning
confidence: 93%
“…Also, results are not entirely consistent across studies, with the conservation of CDE associated with AFS varied from 13.5% to 40% [ 13 , 15 , 17 , 18 ]. However, most studies are conducted on different phacoemulsifiers, which might cause potential bias and reduce the credibility of the results [ 14 , 15 , 17 ]. A similar situation occurs in the reports on other surgical outcomes such as corneal endothelial cells, postoperative IOP and the retinal vasculature [ 18–20 ].…”
Section: Introductionmentioning
confidence: 93%
“…The active-fluidics system has been put into use for many years, but it is not yet widespread 15 21 32. Most of the researches on it are laboratory studies, or focusing on intraoperative parameters; there are few studies on the results and injuries of the surgery 12 16 18 33. In order to fully evaluate changes caused by the active-fluidics system in phacoemulsification, more items need to be taken into account.…”
Section: Discussionmentioning
confidence: 99%
“…[629] A recent study by Oh et al comparing active-fluidics phacoemulsification system with gravity-based system found that there was a statistically significant difference between them, with active-fluidics offering better surgical and visual outcomes. [30] Moreover, in higher nuclear grades of cataracts (3 and more), visual outcomes were superior with the active-fluidics system. [30] Studies have also reported comparable surgical complications in higher nuclear densities.…”
Section: Discussionmentioning
confidence: 99%
“…[30] Moreover, in higher nuclear grades of cataracts (3 and more), visual outcomes were superior with the active-fluidics system. [30] Studies have also reported comparable surgical complications in higher nuclear densities. [63132] An animal study had showed that the amount of “chatter” was lesser with the active-fluidics technology, and it was recommended that lesser torsional power may be required than gravity-based systems.…”
Section: Discussionmentioning
confidence: 99%